An Experimental Apparatus for Monitoring Radon during Compression of Coal/Rock Samples and Its Preliminary Application - Wei Zhang; Kaidi Xie; Yanchao Zhu; Yandong Zhang; Xu Duan; Jibo Zhu (Advances in Civil Engineering)
Based on the radionuclide distributions in sedimentary coal-bearing strata, this study analyzed the microrelease mechanisms of radon in coal-bearing strata. It was found that the microrelease process includes three stages: emanation, migration, and exhalation. Based on this, an experimental apparatus was independently designed for monitoring radon during compression of coal/rock samples from coal-bearing strata, whose major components include an electrohydraulic servocontrolled rock mechanics testing system, an airtight container, coal/rock samples, radon output device, and a continuous emanometer. The developed apparatus was preliminarily utilized for uniaxial compression tests on mudstone samples taken from the #21105 coalface of the Fourth Coal Mine in Yili Coalfield, China. The test results show that before sample failure under the uniaxial compressive load (UCL), the radon concentration is negatively correlated with the applied UCL and the magnitude of imposed elastic deformation. Increasing the applied load shortens the period of stable deformation, gradually decreasing the porosity of the rock, and as a result of declining the concentration of radon emanation from the rock. Finally, suggestions for future research are proposed, including mathematical equations to express the correlations between different experimental parameters and fractal characteristics of radon release from porous media.